Monitoring the Progression of Chronic Liver Damage in Rats Using [18F]PBR06. - Huang, Shuo; Li, Chao; Guo, Jun; Zhang, Linlin; Wu, Shuqi; Wang, Hui; Liang, Sheng (Molecular Imaging & Biology, 2019)
Purpose: Accurate and rapid assessment of liver condition is the key to therapy for hepatitis patients. This study aim is to evaluate the peripheral benzodiazepine receptor (PBR) radioligand [18F]N-fluoroacetyl-N-(2,5-dimethoxybenzyl)-2-phenoxyaniline ([18F]PBR06) as a positron emission tomography (PET) imaging tracer of chronic liver damage in a rat model.Procedures: A rat model of liver damage was made by bile duct ligation (BDL), which initiates a complex cascade of pathological events that leads to cholestasis and inflammation, eventually resulting in a severe fibrotic and severe hepatocyte injury. PET scanning, immunofluorescence staining, H&E staining, Masson's staining, and Quantitative real time polymerase chain reaction(qRT-PCR) were performed to elucidate the correlation among the expression level of PBR, radioactivity uptake, and the level of liver damage in the rat model of chronic inflammatory.Results: Alanine aminotransferase (ALT), aspartate aminotransferase (AST), and total bilirubin (TBIL) increased after BDL and peaked in 1 week, then gradually decreased over the following 3 weeks, although still higher than that of control (all P < 0.05). Histological analysis demonstrated chronic severe damage in rat livers after BDL. The uptake of [18F]PBR06  increased in livers and was correlated with severity of liver damage. Further, the mRNA level of PBR was obviously higher compared to controls.Conclusions: [18F]PBR06 can serve as a sensitive probe to monitor the progression of inflammation in liver. [18F]PBR06 imaging may be used to accurately assess liver damage degree and guide the therapeutic schedule, especially for those patients with severe liver inflammation and damage but with normal or mildly elevated serum ALT and AST. As a non-invasive diagnostic application, [18F]PBR06 PET scan could be an alternative for patients who is unwilling to perform liver biopsy.